ASSESSMENT OF THE LEVEL OF SEMINAL ZINC AND FRUCTOSE CONCENTRATION IN SEMINAL PLASMA OF VIETNAMESE INFERTILE MEN. - Nguyen Thi Trang, Trieu Tien Sang, Nguyen Hoang, Nguyen Tan Gia Khanh & Tran Trung Duc (International Journal of Research Science and Management, 2018)
This study assesses the association between the fructose and zinc concentration and various seminal characteristics. Fructose and zinc in semen reflects the secretory function of seminal vesicles. These Tests may help in assessing the diagnosis and the management of male infertility. Gather semial plasma of 180 males with average age of 31.1 ± 3,6 years old. Use the specific complexant to form a stable coloured complex with fructose or zinc. The colour intensity in a determining wavelength is proportional to the amount of fructose or zinc present in the sample. Seminal fructose concentration was significantly lower in oligozoospermic group and the azoospermic group in comparision with normozoospermic group. There are also many significant differences in Zinc’s concentration in semen when compared two in term of three groups, consist of the oligospermic, azospermic and normospermic group. Sperm DNA fragmentation index in-group with normozospermia correlated positively with seminal fructose (r = 0.47, P < 0.05) and negatively with semianl zinc (r = -0.56, P < 0.05) concentrations. In group with oligozospermia found negative correlation (r = -0.24, P < 0.05) between seminal fructose with sperm DNA fragmentation. In addition, there were 3 patients with Klinefelter syndrome in non-obtructive azoospermia group that had elevated semianal fructose concentration. The role of seminal fructose concentration does not only lie in the assessment of seminal vesicle dysfunction but also in conjunction with other seminal properties could give a useful indication of male reproductive function whilst seminal zinc concentration might not be most appropriate for the assessment of male reproductive dysfunction. This is the first study to demonstrate that the increase of seminal fructose and decrease of zinc concentrations may reflect hight sperm DNA damage. This is the first report of increased in seminal fructose concentration in seminal plasma from the azoospermic men with Klinefelter's syndrome.